Sagot :
Answer:
C. 3, -2
Step-by-step explanation:
The standard form of quadratic equation is x2 – x – 6 = 0 .
By using factorization of quadratic equation for the equation x2 - x – 6 = 0 and splitting the middle term we get, x2 - x – 6 = 0
⇒ x2 + 2x - 3x - 6 = 0
⇒ x (x + 2) - 3 (x + 2) = 0
⇒ (x - 3) (x + 2) = 0
Now, we use the zero product property.
We can have two cases:
⇒ x - 3 = 0 or, x + 2 = 0
Hence, we have two solutions: x = 3 and x = - 2.
You can use Quadratic Equation Calculator to find the roots of a quadratic equation.
Thus, the solutions for the equation x2 – x – 6 = 0 using zero product property is x = 3 and x = - 2.